A novel rhodamine B fluorescence probe for rapid identification of different amino acids by high efficiency fluorescence spectrum-mass spectrometry - Duan, Xiujie; Jin, Tao; Mao, Boneng; Shao, Shihe; Zhao, Lei (Frontiers in Chemistry, 2024)
Rapid detection of amino acids plays an important role in the field of medical diagnosis. By combining Rhodamine B with triphenylamine, a novel double-response fluorescence probe (E)-4- ((4-(((3',6'-bis(diethylamino)-3-oxospiro[isoindoline-1,9'-xanthen]-2-yl)imino)methyl)phenyl)(phe nyl)amino)benzaldehyde (RBTPA) was prepared for rapid identification of different amino acids.Under daylight and 365 nm irradiation, it was found that the color change was most bright at pH=3, and changed to dim at pH=4. When pH=3 and pH= 4, the photophysical properties of the two strong acids are very different. The maximum redshift of UV absorption light is 110 nm, and the maximum fluorescence emission intensity is 4 times different. In order to further observe their binding structure analysis with different amino acids, qualitative analysis of each response structure was determined by mass spectrometry according to different molecular weights. The fluorescence probe RBTPA has two different isomers for recognition response in aldehyde group and imine group, respectively.